GOVERNMENT BUREAUCRACY ETHICS IN PERSPECTIVE NEOCLASSICAL POLITICAL ECONOMY - Eli Apud (Journal of Politica Governo, 2024)
Eoclassical political economy is an important school of thought in the history of economics. It has made significant contributions to our understanding of economics, but has also been criticized by various parties. Neoclassical political economy is the dominant school of economic thought in the world today. It emphasizes the importance of free markets and the price mechanism in determining the allocation of resources. Neoclassical political economy is an influential school of economic thought in the world. This school has strong basic principles, but has also been criticized by various parties when it comes to the perspective of government bureaucratic ethics, a set of values and norms that regulate the behavior of state apparatus in carrying out their duties and functions. The ethics of government bureaucracy is very important to build public trust.